TINJAUAN ULANG PRASASTI YUPIT - Supraptiningsih (BRIN, 1994)
Two Yupit inscriptions were found in Klaten Regency, Central Java, with different places and times. The first Yupit inscription was found in 1989 in the courtyard of the Masjid Dusun Sogaten, Ngawen Village, Klaten Utara District. The second Yupit inscription was found in Kauman Hamlet, Ngawen Village, North Klaten District in 1991. The author reveals this in more depth. Apart from repeating what I have read, I also want to try to provide an idea of ​​the existence of the two inscriptions. Both Yupit inscriptions can be classified in the form of short inscriptions, because their contents are very short, namely only mentioning the number of years / calendar elements of the inscription making, the name of the rank and the name of the village that is used as sima. Inscriptions written on a phallus-shaped stone, such as the Yupit inscription, are usually used as an area boundary bounded by three phallus stones.